Tratado OMPI sobre Propiedad Intelectual/Recursos Genéticos/ Conocimientos Tradicionales Asociados - Michaus R., Martín (2025)
At the 2024 WIPO Diplomatic Conference, after 25 years of negotiations between megadiverse countries and users of genetic resources, the “Treaty on Intellectual Property, Genetic Resources, and Traditional Knowledge Associated with Genetic Resources” was approved. Its goal is to improve the quality of the patent system in these areas and prevent erroneous grants. To achieve this, it establishes two mechanisms: the “Disclosure Requirement” and “Information Systems.” The first was widely debated, while the second requires support for patent offices and Indigenous peoples. This study analyzes its implications, implementation, and relationship with agreements such as the Nagoya Protocol and TRIPS.